The castle in Podhorce in the years 1865 -1939. The state of research and the research postulates - Paduch, Katarzyna (Saeculum Christianum. Pismo Historyczne, 2021)
The Castle in Podhorce has been, and remains, the subject of many studies and articles, but not all aspects of the history of this residence have been studied. This paper presents the state of research on the history of the Castle in Podhorce in the years 1865-1939. The period of ownership of the palace by Princess Constance of Zamoyskich Sanguszko (1864-1946) and Stanislaw Eustachy Sanguszko (1842-1903) still is to be researched. For researchers of the history of the residence in Podhorce the most difficult challenges are related to the detailed examination of the source documents presenting fortunes of the palace against the background of important historical events. In the years 1865-1939 turning points for the Castle in Podhorce were: World War I, the War of 1920, the commemoration of the 250th anniversary of the Battle of Vienna and the outbreak of World War II. However the administration and care of goods in Podhorce is the issue least studied.